Hubungan Sikap Remaja Putri Tentang Pramenstruasi Syndrom dengan Gejala Pramenstruasi Syndrom pada Siswa SMA Assanadiyah Palembang Tahun 2020 - Mariyam Mariyam; Junawalia Mayang Sari; Angges Angges (Universitas Pahlawan Tuanku Tambusai, 2022)
PMS (Premenstrual Syndrome) is a symptom experienced by women 1-2 weeks before menstruation. Most women more than 90% experience premenstrual symptoms such as bloating, headaches and sadness. These symptoms can affect women who are lazy to move. Many young women do not understand the importance of attitude in overcoming the symptoms of premenstrual syndrome, so they are not treated thoroughly. Negative attitudes in dealing with premenstrual syndrome will influence overcoming the premenstrual syndrome period. The aim of this study was to find out the relationship between the attitudes of young women about premenstrual syndrome and the symptoms of premenstrual syndrome in female students at Assanadiyah Palembang High School in 2020. The research used the Analytic Survey method with a Cross Sectional Study Approach. The research population was all young women totaling 117 respondents. The results of the study showed that there were 62 female adolescents who had a positive attitude towards the symptoms of premenstrual syndrome (52.9%) compared to female adolescents who had a negative attitude towards the symptoms of premenstrual syndrome, namely 55 persons (47.1%). More teenage girls experienced symptoms of premenstrual syndrome, namely 61 people (52.1%), compared to young women who did not have symptoms of premenstrual syndrome, namely 56 people (47.9%). The results of the Chi-Square statistical test obtained a p_value (0.004) < α (0.05), which means that there is a significant relationship between the attitudes of young women about premenstrual syndrome and the symptoms of premenstrual syndrome at SMA Assanadiyah Palembang. It is hoped that young women can increase their knowledge and education about attitudes towards premenstrual syndrome or symptoms before menstruation, both physically and psychologically. Keywords: Attitude of young women, premenstrual syndrome.